Skills, migration, and industrial structure in a dual economy - Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2013)
A comparative-static model describes the decline of manufacturing in the face of rising overseas employment through a mechanism other than the Dutch Disease. Instead it is competition for skilled labour and the relative ease in producing skills that affect the size of the manufacturing sector, including its employment of unskilled labour.
Keywords: O14; O15; 330; deindustrialisation; manufacturing and services sector; migration; skills; Deindustrialisierung; Brain Drain; Humankapital; Industrie; Industriestruktur; Dualökonomie; Theorie